2014
DOI: 10.14687/ijhs.v11i2.3093
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of pilates exercise programs on flexibility performance and body composition in women<p>Bayanlara uygulanan pilates egzersiz programının esneklik performansı ve beden kompozisyonu üzerine olan etkisinin incelenmesi

Abstract: The aim of this study was to investigate the effect of the Pilates training program on flexibility and body composition in women. A total of 62 volunteer women participated in this study. Women were divided into 2 groups as experimental (32 women) and control groups (30 women). The body weights, Body mass index and flexibility performances were measured before and after the program. To measure the flexibility performance, the SitStretch Test was used. Both experimental and control groups has regularly particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As a result of the literature research, it was found out that clinical, reformer pilates exercises had an effect on flexibility values during the training period (Chinnavan et al, 2015;Baştuğ et al, 2014;Aslanoğlu and Şenel, 2013;Demir and Çilli, 2018;Rogers and Gibson, 2009;Karadenizli and Kamur, 2016;Katayıfçı et al, 2014), BMI (Body mass index) is effective in the values (Baştuğ et al, 2014;Abramaviči et al, 2013;Jago et al, 2006), decreased body fat percentage values (Aslanoğlu and Şenel, 2013;Abramavičiūtč et al, 2013;Sekendiz et al, 2006;Jago et al, 2006), which are effective in muscle strength parameters (Aslanoğlu and Şenel, 2013;Abramavičiūtč et al, 2013;Sekendiz et al, 2006;Rogers and Gibson, 2009;Katayıfçi et al, 2014), the physical fitness parameters of the environment, skin fold measurement, waist hip ratio, body composition values are effective on (Rogers and Gibson, 2009;Katayıfçı et al, 2014 ;Liman and Güzel, 2008;Gökç elik, 2017) and the Pilates exercise to be effective in physiological parameters (Liman and Güzel, 2008;Temur et al, 2018), has also been found to be effective on balance performance (Katayıfçı et al, 2014;Demir and Çilli, 2018;Atılgan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the literature research, it was found out that clinical, reformer pilates exercises had an effect on flexibility values during the training period (Chinnavan et al, 2015;Baştuğ et al, 2014;Aslanoğlu and Şenel, 2013;Demir and Çilli, 2018;Rogers and Gibson, 2009;Karadenizli and Kamur, 2016;Katayıfçı et al, 2014), BMI (Body mass index) is effective in the values (Baştuğ et al, 2014;Abramaviči et al, 2013;Jago et al, 2006), decreased body fat percentage values (Aslanoğlu and Şenel, 2013;Abramavičiūtč et al, 2013;Sekendiz et al, 2006;Jago et al, 2006), which are effective in muscle strength parameters (Aslanoğlu and Şenel, 2013;Abramavičiūtč et al, 2013;Sekendiz et al, 2006;Rogers and Gibson, 2009;Katayıfçi et al, 2014), the physical fitness parameters of the environment, skin fold measurement, waist hip ratio, body composition values are effective on (Rogers and Gibson, 2009;Katayıfçı et al, 2014 ;Liman and Güzel, 2008;Gökç elik, 2017) and the Pilates exercise to be effective in physiological parameters (Liman and Güzel, 2008;Temur et al, 2018), has also been found to be effective on balance performance (Katayıfçı et al, 2014;Demir and Çilli, 2018;Atılgan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%